Perbedaan Penerapan Pendekaran Per se Illegal dan Rule of Reason dalam Putusan KPPU tentang Kartel Penetapan Harga - Dimas Aryadiputra; Deny Slamet Pribadi; Aryo Subroto (Fakultas Hukum Universitas Mulawarman, 2022)
The emergence of an economic impact analysis in the decision of the price fixing cartel case in Article 5 of the UULPM which should use the approach in that article is Per se Illegal, including Decision No. 08/KPPU-L/2018, Decision No. 04/KPPI-I/2016, Decision No. 32/KPPU-L/2008, Decision No. 26/KPPU-L/2007, and Decision No. 02/KPPU-I/2003 by analyzing the use of a single Per se Illegal approach in the decision of the price fixing cartel case in ensuring legal certainty. The approach in this study uses doctrinal research. From the results of the analysis of the decision related to the price fixing cartel in the consideration of the commission assembly, it has been found in the form of economic evidence/economic analysis which is a characteristic of the Rule of Reason approach to the reasons for the emergence of the economic analysis not being explained explicitly and clearly by the commission assembly, regarding the assessment that can be made. carried out by the KPPU regarding the agreement in Article 5 of the UULPM, economic evidence may appear if the requirement to prove the agreement is difficult to find. Legal considerations using the Per se Illegal approach as the sole approach in the KPPU's decision related to price fixing cartels in ensuring legal certainty, this has been in line with what is positively regulated in Article 5 of the UULPM wherein the provision contains the phrase